2021
DOI: 10.1158/0008-5472.can-21-1987
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ribonucleotide Reductase Induces Synthetic Lethality in PP2A-Deficient Uterine Serous Carcinoma

Abstract: Disclosure of Conflict of Interest: C.M. O'Connor and G. Narla are named inventors on a US provisional patent application concerning compositions and methods for treating high grade subtypes of uterine cancer. C.M. O'Connor, T.K. Suhan, K.P. Zawacki, and J. Sangodkar are consultants for RAPPTA Therapeutics. G. Narla is chief scientific officer at RAPPTA Therapeutics, is an SAB member at Hera BioLabs, reports receiving commercial research support from RAPPTA Therapeutics, and has ownership interest (including p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
1
8
3
Order By: Relevance
“… 239 In 2020, the derivative of SHP099, TNO155, went into clinical trial for the treatment solid tumor. 240 In addition to PTP1B and SHP2 inhibitors, there are few drugs targeting other phosphatases, and only a few drugs such as PRL3-zumab 241 (anti-PRL3 antibody), and LB-100 242 (PP2A inhibitor) have advanced to the clinical stage (Fig. 2 , Table 3 ).…”
Section: Progress In Innovative Pharmacological Approaches That Targe...mentioning
confidence: 99%
“… 239 In 2020, the derivative of SHP099, TNO155, went into clinical trial for the treatment solid tumor. 240 In addition to PTP1B and SHP2 inhibitors, there are few drugs targeting other phosphatases, and only a few drugs such as PRL3-zumab 241 (anti-PRL3 antibody), and LB-100 242 (PP2A inhibitor) have advanced to the clinical stage (Fig. 2 , Table 3 ).…”
Section: Progress In Innovative Pharmacological Approaches That Targe...mentioning
confidence: 99%
“…To date, nucleoside analogues are not routinely considered as treatment for patients with EC, although gemcitabine is sometimes used as a second-line or later-line therapy [24]. With this study, we showed that nucleoside analogues show potential to become a more valuable treatment option for patients with type II EC and should be investigated more thoroughly in pre-clinical studies.…”
Section: Discussionmentioning
confidence: 68%
“…Conversely, Aα WT overexpression in the PPP2R1A mutant cell lines resulted in increased resistance towards clofarabine. Therefore, this study suggested the use of the PPP2R1A mutational status as a positive predictive marker for treatment of EC patients with clofarabine [24].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, loss of PTPA was found to sensitize to mTOR inhibitors, loss of B55α ( PPP2R2A ) and B56α ( PPP2R5A ) sensitized to poly adenosine diphosphate-ribose polymerase inhibitors (PARPi) (veliparib), Checkpoint Kinase 1 (Chk1) inhibitors (SB218078), and ATR inhibitors ( 185 , 186 , 187 , 188 , 189 , 190 ). Lastly, PP2A Aα mutants were found to sensitize to ribonucleotide reductase inhibitors, including Gemcitabine and Clofarabine ( 191 ). Collectively, these approaches illustrate that PP2A-inactivated tumors may be targeted using synthetic lethal based strategies, and PP2A activity may play a significant role in the development of therapy resistance.…”
Section: Therapeutic Targeting Of Pp2amentioning
confidence: 99%